Is China destined to play high-politics in East Asia? - Karim, M.A. (2015)
The aim of this paper is to project China’s emerging trend towards high-politics in East Asia that is ostensibly generated by regional geopolitical dynamics. Hegemonic transition, replacing hegemonic stability, may seemingly be activating the dynamics. There is almost an inexorable move towards high-politics due mainly to presence of issues that are likely to trigger conflict, possibly a limited war. These issues range from flash points to populist nationalism, economic interdependence, and a competition for supremacy in the Western Pacific. The paper concludes by highlighting likely resultant hi-politics, action-reaction cycles, polarizations and alignments by arraying of forces, probability of a limited war, mutual deterrence, and projecting overall power relations.